A study on the use of system in Chemi-Con (M) Sdn Bhd / Noor Ernna Mohd - Mohd, Noor Ernna (Faculty of Business and Management, 2011)
This paper discusses the potential to upgrade the 3A Accounting System for companies and organizations. By replacing outdated accounting systems with more powerful solutions, small and mid-sized businesses can reap many benefits which are higher efficiency, more productivity, and faster growth. A successful systems upgrade depends on several key factors: adequate planning, a realistic budget, the proper technology and a knowledgeable solution Provider, this study also discusses about comparison between system that practiced by this company and also some recommendation to improve their accounting systems.